Dense Water Formation in the North–Central Aegean Sea during Winter 2021–2022 - Manos Potiris; Ioannis G. Mamoutos; Elina Tragou; Vassilis Zervakis; Dimitris Kassis; Dionysios Ballas (Journal of Marine Science and Engineering, 2024)
The evolution and drivers of dense water formation (DWF) in the North–Central Aegean Sea (NCAeg) during winter 2021–2022 are studied using observations from two Argo floats and the output of an operational data-assimilating model. Dense water with <semantics>σθ>29.1 kgm−3</semantics> was produced over most of the NCAeg, except for the northeastern part covered by Black Sea water (BSW), where the maximum surface density was <semantics><29 kgm−3</semantics>. The highest density waters were produced over the central and southern parts of the Lemnos Plateau and in the shallow coastal areas between Chios Island and the Edremit Gulf. Atmospherically driven transformation to the east of Lesvos Island resulted in the production of waters with anomalously high density and salinity, which flowed inside Skiros Basin, thus partly explaining its historically higher density and salinity compared to the rest of the NCAeg subbasins. The Skiros and Athos Basins were ventilated down to <semantics>σθ</semantics>∼<semantics>29.35 kgm−3</semantics> horizons. The <semantics>29.1 kgm−3</semantics> isopycnal rose by ∼<semantics>200 m</semantics>, and the <semantics>29.25 kgm−3</semantics> isopycnal overflowed above the ∼<semantics>400 m</semantics> sill depth filling the southern depressions of the NCAeg. Combining data from Argo floats, vessel casts, gliders, and a fixed-point observatory, the dense water produced in the NCAeg was observed spreading in the deep layer of the Central Cretan Sea for at least one and a half years after the formation. The cyclonic circulation of the newly formed water in the NCAeg has been observed directly for the first time using deep-drifting floats. The Eastern Mediterranean warming and salinification signal has propagated below the NCAeg sill depth. The winter average buoyancy loss was comparable to that of the peak of the Eastern Mediterranean transient (EMT) and other known years of DWF in the NCAeg; however, the high temperature of the upper layers due to long-term warming prevented the widespread formation of denser water.